Dual closed-loop sliding mode control for a decoupled three-link wheeled mobile manipulator. (September 2018) - Seo, In Seok; Han, Seong Ik
Abstract: This paper presents a dual closed-loop sliding mode control strategy for a wheeled mobile manipulator with three-wheeled mobile platform (WMP) and three-link manipulator. The Euler-Lagrange method combined partially with the Newtonian method is applied to obtain full dynamic model and decoupled model is constructed in order to provide simple dynamic model for controller's structure to be simplified. Instead of the conventional velocity command trajectory based kinematic backstepping control method, a dual closed-loop control system is designed. A virtual velocity command based on sliding mode surface is generated in outer loop and the gap between a generated virtual command velocity and real velocity is compensated by an inner loop sliding mode controller. Outer loop helps to faster posture trajectory generation for locomotion of the WMP. Next, a finite-time sliding mode controller with an assumed feedforward dynamic gain method is designed for joint trajectory tracking for three-link manipulator by adding finite-time control terms in the designed controllers to obtain faster settling time and stronger robustness. The designed controllers were implemented into microprocessor connected to DC and dynamixel motor systems equipped in mobile platform and manipulator, respectively. Comparative simulation and experiment with a conventional sliding mode control show the effectiveness of the proposed dual closed-loop finite time sliding mode control scheme. Highlights: The full dynamic model of the wheeled mobile manipulator is constructed and its model is decoupled as two parts. By generating virtual velocity command, an outer loop SMC is designed to provide more intuitive posture tracking trajectory of the wheeled mobile platform than the conventional velocity tracking backstepping method. A modified finite-time sliding mode controller is designed to guarantee finite-time convergence and robustness to uncertainty. New simulation and real experiment for the mobile manipulator system were conducted.